1994
DOI: 10.1159/000187824
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Proteolytic Activity of Factor D Accumulated as an Active Serine Protease in Patients with Chronic Renal Failure

Abstract: Complement factor D, a complement system serine protease, circulating in vivo as its active form, accumulates in patients with chronic renal failure. The pathophysiological role of this active protease in these patients was examined by studies on activities of excess factor D on 10 synthetic peptide substrates for some usual serine proteases. The most sensitive of these substrates to factor D was Boc-Gln-Ala-Arg-MCA, which is used as a substrate for trypsin. The proteolytic activity of factor D (2.17 unit/mg/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Our results show that expression levels of CFD in rat urine, kidney tissue, and clinical samples were increased by progression of diabetic nephropathy. It is known that plasma concentrations of CFD increase up to 10-fold in the end stage of renal failure, suggesting that its metabolism is related to renal functions [ 42 , 43 , 44 ]. CFD metabolism in patients showed that the proportion of CFD elimination in the urine was increased in patients with tubular dysfunctions, it demonstrated that under normal circumstances CFD is filtered through the glomeruli and reabsorbed by tubular cells [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that expression levels of CFD in rat urine, kidney tissue, and clinical samples were increased by progression of diabetic nephropathy. It is known that plasma concentrations of CFD increase up to 10-fold in the end stage of renal failure, suggesting that its metabolism is related to renal functions [ 42 , 43 , 44 ]. CFD metabolism in patients showed that the proportion of CFD elimination in the urine was increased in patients with tubular dysfunctions, it demonstrated that under normal circumstances CFD is filtered through the glomeruli and reabsorbed by tubular cells [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that adipsin plasma levels increase ≈10-fold in end-stage renal failure, suggesting that its metabolism is closely linked to the renal functions. [18][19][20] Pascual et al 21 studied adipsin metabolism in humans by injecting purified radiolabeled adipsin into 5 healthy individuals and 12 patients with various renal diseases or renal failure. The proportion of adipsin elimination in the urine was increased in patients with tubular dysfunction, indicating that under normal circumstances adipsin is filtered through the glomeruli and reabsorbed by tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Substrates. It has previously been shown that Factor D possesses extremely low activity toward activated peptide substrates such as peptide p-nitroanilides (20) and thioesters (8). We have explored the activity of Factor D toward a group of synthetic substrates, including a direct comparison of the reactivities of Factor D and of trypsin toward some of the same substrates, to better quantify this aspect of the reactivity of the enzyme.…”
Section: Activity Of Factor D Toward Thioester and P-nitroanilidementioning
confidence: 99%